Intimate Partner Violence and Housing: Eroding Women’s Citizenship - Zufferey, C.; Chung, Donna; Franzway, S.; Wendt, S.; Moulding, N. (Sage, 2016)
Intimate partner violence (IPV) is an extreme example of gender inequality that compromises women’s citizenship. This article discusses the effects of IPV on women’s housing circumstances based on the findings of a large national Australian survey. The analysis found that IPV erodes women’s citizenship, which includes their access to safe and affordable housing, connections to “home,” and participation in community life. Drawing on notions of gendered citizenship, this article provides new understandings about how women negotiate housing as a key dimension of citizenship in the context of IPV.